The infographic guide to American government : a visual reference for everything you need to know - Lytle, Carissa; Kern, Jara (Adams Media, 2019)
"This graphic reference guide breaks down the ins and outs of American government, explaining the details and revealing the exciting backstory of prominent events, concepts, and figures, including: Checks and balances; The Electoral College; Three branches of government; Red states, blue states, swing states; The Supreme Court; Freedom of the press ... and many more! The Infographic Guide to American Government is an illustrated take on how America is run"--Page 4 of cover.